CATUR DIMENSIONAL STRATEGIC DA'WAH (CDS) (CONCEPT, ANALYSIS, AND APPLICATION) - Agung Drajat Sucipto (International Journal of Multidisciplinary Reseach, 2026)
Da’wah is a noble calling whose essence is intrinsic to the very existence of Islam. It represents an organized effort to translate divine values ​​into human reality. In practice, however, this calling often confronts complex challenges. Globalization, the digital revolution, shifting social values, and the growing diversity of thought within society necessitate adaptation and innovation in da’wah. Relying solely on zeal without a foundation of sound knowledge risks rendering the effort ineffective, irrelevant, or even counterproductive to its objectives. Through this qualitative literature-based study, the researcher aims to map out a structured framework regarding the scholarly dynamics of da’wah. The discussion begins by dissecting the fundamental meaning of da’wah, examining both its etymological roots and definitions formulated by scholars. This exploration is crucial for establishing a solid conceptual foundation and avoiding the reductionist interpretations of da’wah often found in society. A precise understanding of da’wah enables a clear identification of the scope of its study. Ultimately, this research maps the complexities of da’wah through an integrated framework known as the Catur Dimensi-Dakwah Strategis (CDS) or the Four-Dimensional Strategic Da’wah framework. This framework categorizes the analysis of da’wah into four interconnected dimensions. First is the Theological-Normative Dimension, which examines the foundations, ethics, and objectives of da’wah in accordance with the Qur'an and Sunnah. Second is the Psycho-Sociological Dimension, which analyzes the psychological states and social contexts of both the subjects and objects of da’wah. Third is the Managerial-Organizational Dimension, which views da’wah as an activity requiring professional management. Fourth is the Technological-Contextual Dimension, which focuses on adapting da’wah to modern media and the challenges of the times.